2007
DOI: 10.1111/j.1475-3588.2006.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioural Therapy for Anxiety Disorders in Children and Adolescents: A Meta‐Analysis

Abstract: We conducted a meta-analysis using 20 randomised controlled studies of cognitive behavioural therapy (CBT) for anxiety disorders in children and adolescents. The mean pre-post effect size was d ¼ 0.94, which was maintained at follow-up. The mean effect size when comparing the CBT and control group was d ¼ 0.61. Within the CBT group, the mean effect size of university clinics (d ¼ 0.77) was larger than that of other clinics (d ¼ 0.37). The difference in effect sizes was hardly noticeable when comparing CBT with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(123 citation statements)
references
References 49 publications
10
105
0
7
Order By: Relevance
“…[6,18,19] Several studies have compared individual CBT to group CBT [20,21,22] in children older than 8 years of age with both individual and group therapies appearing effective in the treatment of anxiety disorders although in one study [21] socially anxious children responded better to individual treatment rather than group treatment. It is important to note, however, that whether individual or group CBT is a better treatment modality is a relatively underresearched area and results to date are far from conclusive.…”
Section: Cognitive Behavioral Therapy For Anxiety Disordersmentioning
confidence: 98%
“…[6,18,19] Several studies have compared individual CBT to group CBT [20,21,22] in children older than 8 years of age with both individual and group therapies appearing effective in the treatment of anxiety disorders although in one study [21] socially anxious children responded better to individual treatment rather than group treatment. It is important to note, however, that whether individual or group CBT is a better treatment modality is a relatively underresearched area and results to date are far from conclusive.…”
Section: Cognitive Behavioral Therapy For Anxiety Disordersmentioning
confidence: 98%
“…In typically developing children with anxiety disorders, self-report of anxiety is also less sensitive to treatment change than parent and clinician ratings. For example, the average child self-report was d = 0.36 in 1 meta-analysis 59 and d = 0.44 in the other. 60 Regarding the discrepancy between parent and child reports of anxiety, it is noteworthy that cross-informant disagreements are a norm rather than the exception in assessment of child psychopathology.…”
Section: Figurementioning
confidence: 99%
“…Principal aims for parental involvement are: removal of parental reinforcement of anxious child behavior, teaching anxiety management skills to parents, and reduction of family conlicts [74]. Reviews [74,76,77] and meta-analyses [73,[78][79][80] have suggested that family-based CBT is eicient for the treatment of childhood anxiety; on the other hand, there are no diferences in the outcomes among individual, group, or family-based treatment [75].…”
Section: Parental Involvement In Cognitive Behavior Therapy For Intermentioning
confidence: 99%